Exploratory Study on the Competencies in Sustainability of Secondary School Students Facing Conflicts Associated with 'Fast Fashion' - Isabel Banos-González; Patricia Esteve-Guirao; Ana Ruiz-Navarro; María Ángeles García-Fortes; Magdalena Valverde-Pérez (MDPI AG, 2024)
This exploratory study analyses the level of the development of the eight key competencies in sustainability of 237 students in the 7th-10th grades, when confronted with a real conflict situation associated with the production and consumption of 'fast fashion'. Their responses were categorised into four levels, representing the degree of development of each competence. The results reflect a low level of competence development, with no significant differences among academic year groups. The competence where the highest level of development was reached was the inter-personal competence, as students recognised that the consumption of fast fashion contributes to the labour exploitation of others. However, this did not prompt students to question the prevailing consumerist values in our society (values-thinking competence), their own practises (implementation competence), or their own contribution to the problem (intra-personal competence). Therefore, it seems necessary to address different socio-environmental issues, critically analyse our daily actions, and thus promote these competencies in sustainability in schools. These will enable students to actively participate in environmental conservation from the perspective of environmental and social justice.